Initiating a Grounded Theory Study: Scoping the Area of Interest, Overcoming Hurdles in the Ethics Review, and Initial Data Collection - Gudrun Reay (Grounded Theory Review: An International Journal, 2024)
A well-executed grounded theory study requires thoughtful planning coupled with an awareness that grounded theory research rests on a foundation of emergence and openness to where the data leads the investigator. Grounded theory allows for multiple sources of data that offer insight into the topic and aid in theory development. Scooping the area of interest offers an opportunity to explore diverse sources where data can be found and lays the foundation for writing a successful ethics application. Writing a grounded theory ethics application entails overcoming hurdles such as, navigating how to formulate the research question so it is sufficiently open to allow for what emerges during the study as important to the participants, estimating sample size when this cannot be known beforehand in grounded theory, and providing a list of and rationale for data sources. This article offers insights into how to scope the area of interest, guidance on how to complete an ethics application, and advice on how to initiate data collection with special attention given to conducting interviews and observations.